Performance evaluation of reduced graphene oxide incorporated dye-sensitized solar cells for stable power generation - Ikpesu, Jasper Ejovwokoghene (University of the Witwatersrand, Johannesburg, 2024)
Dye-sensitized solar cells (DSSCs) have emerged as a promising alternative to traditional silicon-based solar cells due to their low cost, easy fabrication, and high efficiency in converting sunlight into electricity. However, the performance of (DSSCs) is limited by the charge transfer and recombination processes at the interfaces between the different components of the device. In the recent years, Graphene Oxide (GO) and reduced Graphene Oxide (rGO) have been proposed as potential interfacial components to improve the performance of DSSCs. This research looked at the performance of reduced graphene oxide in dye-sensitized solar cells for sustained power generation. Most dye-sensitized solar cells have benefited from the usage of reduced graphene oxide. This research focuses on the performance of reduced graphene oxide in dye-sensitized solar cells for sustained power generation. Most dye-sensitized solar cells have benefited from the usage of reduced graphene oxide. This is due to its characteristics such as high surface area, superior transparency in the visible region, light absorption, and charge transport. Aerosol Assisted Chemica1 Vapour-Deposition (AACVD) was used to create a fluorine doped tin oxide (FTO) layer. The Hummer's Method was applied to synthesize reduced graphene oxide (rGO). Titanium (IV) oxide – reduced graphene oxide (TiO2-rGO) composite was synthesized at the photoanode via screen printing and spin coating, then inserted in DSSC using roselle dye as a natural dye sensitizer to investigate the cell performance. X-ray diffraction (XRD), ultraviolet diffuse reflectance spectroscopy, scanning electron microscopy/energy dispersive X – ray (SEM/EDX), and profilometry were used to characterize the synthesized/fabricated samples. Using a solar simulator and air mass A.M. 1.5 (100 mw/cm2), current-voltage (I-V) measurements were obtained to determine the performance of the cells. Tin oxide thin films doped with fluorine (F:SnO2) were successfully deposited on a glass substrate using the AACVD process at various doping percentages and the optical properties of the FTO and substrate layers were investigated using absorbance spectra. A low absorption value of 12% F: SnO2 resulted in a higher transmittance of 90% were achieved. This shows that the optical and electrical properties of the DSSC were altered by fluorine doped tin oxide. The results of the developed spin coated TiO –rGO Nano composites revealed that the Hall Effect increases with thin-film thickness iv while mobility increases with carrier concentration. The optical absorption results of TiO2–rGO nanocomposites demonstrate that as dopant amount increases, the band gap energy falls from 3.6 eV to 1.4 eV. The findings indicate that there is a strong interaction between Titanium dioxide (TiO2) and reduced Graphene Oxide (rGO), which could result in better visible light absorption and consequently improve light harvesting efficiency when utilized in a dye sensitized solar cell. Open circuit voltage (0.53 V), short circuit photocurrent (0.12 mA/cm2), fill factor (0.02), and photoelectric conversion efficiency (11.52%) were the simulation results for the cell parameters obtained for the DSSC manufactured using reduced graphene oxide. Meanwhile, the open circuit voltage (0.56 V), short circuit photocurrent (0.63 mA/cm2), fill factor (0.03), and photoelectric conversion efficiency (4.70%) of the DSSC without reduced graphene oxide were obtained. The power conversion efficiency of the dye-sensitized solar cell with graphene oxide was 6.82 % greater than that of the cell without graphene oxide. A four-week stability test was also performed on the DSSC fabricated with reduced graphene oxide to measure the extent of electrolyte deterioration. After the first 24 days, the short circuit current value reduced by 39% from its original value of 0.1190 mA/cm2. Under white light irradiation, the efficiency value of the DSSCs was found to be stable for the first 12 days before gradually decreasing to 24% of its initial value. The improved performance of DSSCs with reduced graphene oxide may be ascribed to an increase in electron transport efficiency and visible light absorption. When reduced graphene oxide was used, the performance improved due to increased light absorption, a wider range of absorption wavelengths, faster electron transport, and suppression of charge recombination. Based on this research, comparing the absorbance and transmittance of fluorine- doped tin oxide (F: SnO2) at 4%, 8%, and 12% with regard to wavelengths (ℷ) at 230 nm and 1100 nm; It shows that at 12% (F: SnO2), the lowest absorbance yields better transmittance, and increasing the cell's efficiency by 11.52%. The power conversion efficiency (PCE) of DSSCs demonstrates that DSSCs fabricated with reduced graphene oxide improved cell performance and outdoor stability. Which confirm that the TiO2 - rGO is a good material for solar application.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Engineering and the Built Environment, School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Dye-sensitize; (DSSCs); SDG-7: Affordable and clean energy; SDG-9: Industry, innovation and infrastructure